2022
DOI: 10.3389/fpls.2022.849574
|View full text |Cite
|
Sign up to set email alerts
|

Functional Response of Harmonia axyridis to the Larvae of Spodoptera litura: The Combined Effect of Temperatures and Prey Instars

Abstract: Functional responses are central to predator–prey dynamics and describe how predation varies with prey abundance. Functional responses often are measured without regard to prey size (i.e., body mass) or the temperature dependence of feeding rates. However, variation in prey size within populations is ubiquitous, and predation rates are often both size and temperature-dependent. Here, we assessed functional responses of larvae and adult Harmonia axyridis on the 1st, 2nd, and 3rd instars of the prey Spodoptera l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Temperature also affected the predation rate by adult N. kingbergii on P. xylostella but did not alter the functional response type (Ma et al, 2005). Low attack rates or handling times at low temperatures, as observed in our study, can be attributed to reduced effort invested in foraging for prey or longer resting times by the predators (Brown et al, 2004;Pruitt et al, 2011;Nunes et al, 2020;Islam et al, 2022;Lin et al, 2022). As temperatures increase, predator mobility increases, which allows for higher attack and consumption rates (Lang et al, 2012;Nunes et al, 2020;Gvoždík & Boukal, 2021;DeLong & Uiterwaal, 2022).…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Temperature also affected the predation rate by adult N. kingbergii on P. xylostella but did not alter the functional response type (Ma et al, 2005). Low attack rates or handling times at low temperatures, as observed in our study, can be attributed to reduced effort invested in foraging for prey or longer resting times by the predators (Brown et al, 2004;Pruitt et al, 2011;Nunes et al, 2020;Islam et al, 2022;Lin et al, 2022). As temperatures increase, predator mobility increases, which allows for higher attack and consumption rates (Lang et al, 2012;Nunes et al, 2020;Gvoždík & Boukal, 2021;DeLong & Uiterwaal, 2022).…”
Section: Discussionsupporting
confidence: 50%
“…Among others, abiotic factors can influence predator–prey interactions and the functional response of predators to variation in prey density. Temperature variations can significantly change the nature of the functional response of insect predators, and their overall predatory behaviour, as insects are poikilothermic (Sentis et al., 2012; Chen et al., 2019; Islam et al., 2022). Such changes can be attributed to temperature‐driven variations in biochemical and physiological response rates in predators (Laws, 2017; Boukal et al., 2019; Gvoždík & Boukal, 2021) and can change trophic level interactions and energy transfer (Gillooly et al., 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The population parameters and feeding rate of this predator have been shown to depend on the temperature and resource 30 . Using laboratory experiments, we showed that foraging by H. axyridis on the eggs and larvae of S. litura (eggs and larvae) is temperature-derived 23 , 35 . Predator (larvae and adults) increases its foraging with warmer temperatures and decreases with colder temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The family Coccinellidae includes a globally widespread group of predatory beetles that are polyphagous 16 and indicate preference for resource including transitions across kingdoms (Animalia, Fungi, and Plantae) and trophic levels (carnivorous and herbivorous) 17 . Many coccinellids are important predators of hemipterans, including aphids 10,18 , whitefly 19 , mealybugs 20 , scale insects 21 and immature lepidopterans 22,23 . Resource quality, thermal surroundings, mobility 24 , nutritional status 25 , as well as density and size of the prey 26 are critical determinants of predator development, biology 16 and predation parameters 12,[27][28][29] .…”
mentioning
confidence: 99%